O uso do geogebra: um caminho para o ensino de produtos notáveis sob as lentes da teoria dos registros de representação semiótica - Santos, Jussanã Gomes dos (2022)
This is qualitative research that aims to investigate how the different semiotic representations built in the GeoGebra software can favor the teaching of remarkable products, according to the Theory of Semiotic Representation Records. Previous studies point to the importance of teaching Remarkable Products in Elementary School and how not learning about this topic can compromise future learning. In addition, these researches show that generally the approach of Remarkable Products is done in the molds of traditional teaching. In conclusion, these works point to the need for research to be developed to investigate other methodologies to address this issue. Given this scenario, this work seeks to answer the guiding question: How can the GeoGebra software favor the teaching of remarkable products through the lens of the Theory of Semiotic Representation Records? For the construction of this research, the theoretical and methodological design is the Theory of Registers of Semiotic Representation by Raymond Duval. It presents and builds a proposal for teaching the notable products of the square of the sum of two terms, the square of the difference of two terms and the product of the sum and the difference of two terms. Using GeoGebra, it was possible to visualize and access the different semiotic representations, such as algebraic representation, representation in natural language, figural representation, in addition to performing the processing and conversion activities between records almost instantly.